(untitled) (Orfeu, 2018)
There has been considerable research on instrumental practice and musical motivation. This paper aimed to extend this research studying instrument differences in beginner players in relation to their practice and motivation. Almost 500 beginner instrumentalists and vocalists completed a questionnaire which consisted of a number of statements relating to time spent practicing, practicing strategies, organisation of practice, motivation to practice, support for playing an instrument, self-beliefs, musical identity, enjoyment of performance and musical aspirations. Participants, who were divided into seven instrumental groups (strings, woodwind, brass, piano/keyboard, guitar, drummers, and voice) responded on a seven-point Likert scale. Multivariate analysis was undertaken in relation to time spent practicing, practice strategies, attitudes towards practice and motivation. The analyses took account of instrument group, age and gender and showed the complexity of the relationships between these. The findings are discussed in terms of their implications for teaching.